PERENCANAAN STRUKTUR GEDUNG APARTEMEN 5 LANTAI PADA JALAN MAJOR ALIANYANG, KABUPATEN KUBU RAYA (STRUCTURAL PLANNING OF A 5-STORY APARTMENT BUILDING ON MAJOR ALIANYANG STREET, KUBU RAYA REGENCY): PERENCANAAN STRUKTUR GEDUNG APARTEMEN 5 LANTAI PADA JALAN MAJOR ALIANYANG, KABUPATEN KUBU RAYA (STRUCTURAL PLANNING OF A 5-STORY APARTMENT BUILDING ON MAJOR ALIANYANG STREET, KUBU RAYA REGENCY) - Ramadana Putra, Hari; Anggraini, irene; Konstatinus, ayub; Rizky Priandra, Muhammad (RETENSI, 2023)
The development of apartments is very suitable for the millennial lifestyle, which heavily relies on technology,comfort, and compact yet functional home design, especially due to the economic growth of society and thesurge in productive age and millennials. These apartments are planned in Kubu Raya Regency. The structuraldesign is one of the most crucial elements of building planning; reinforced concrete will be used in thebuilding's construction.. The building structure consists of Roof Slab, Floor Slab, Beams, Columns, andFoundation. This apartment structure has five levels, each measuring four meters in height.. This apartmentbuilding is designed to withstand earthquakes and is located on Major Alianyang Street, Kubu Raya Regency,West Kalimantan Province. Earthquake planning uses response spectrum according to SNI 1726-1029. Loadcalculations are in accordance with SNI1727-2020 and PPURG 1987. The requirements for structuralconcrete of the building are according to SNI 2837-2019, and the chosen calculation method for this buildingis the Medium Moment Resisting Frame System (SRPMM). From the calculation results, the thickness of theroof slab and floor slab is 13 cm; sloof beam with dimensions of 35 cm x 70 cm; main beam with dimensionsof 30 cm x 60 cm; secondary beam 1 with a thickness of 20 cm x 40 cm; secondary beam 2 with a thickness of30 cm x 15 cm; column with dimensions of 70 cm x 70 cm; shear wall with a thickness of 30 cm; pilecapfoundation size is 350 cm x 350 cm x 700 cm, while the dimensions of the minipile are 40 cm x 40 cm.Keywords: Reinforced Concrete Structure, Structural Planning, 5-story Building